Analisis SEM (Structural Equation Model) Dalam Manajemen Industri Layanan Kesehatan Menggunakan LISREL dan OSS Statistika-R - Habibi, Azwar; Tirta, I Made; Lestari, Budi (Pendidikan Biologi,Universitas Islam Jember, 2014)
The objective of this research is to know the application of SEM (Structural Equation Model) analysis in seeing reliability and validity of causal relationship among latent variables in the area of marketing management of health service industry influenced by patient perception about health service quality on patient loyality with satisfaction of patient as the medium variable. SEM Analysis is a group of statistical techniques which is conducive to be done examination a relation network which is complicated relative simultaneously. In SEM, we can do three activities simultaneously, that are inspection and validity of reliability equivalent instrument with confirmatory factor analysis, examination of relationship model among latent variables equivalent with path analysis, and get worthwhile model for predicting equivalent with structural model or regression analysis. The conclusion of got from this research is there are influence which significant among the perception of patient to the patient loyality, the perception of patient to the satisfaction of patient, the satisfaction of patient to the patient loyality.Keywords: Structural Equation Model, reliability, validity, confirmatory factor analysis, path analysis.